Evidence of a Causal Relationship Between Body Mass Index and Immune-Mediated and Inflammatory Skin Diseases and Biomarkers: A Mendelian Randomization Study - Li Z; Zhao Y (Clinical, Cosmetic and Investigational Dermatology)
Zhaoyi Li, Yibin Zhao The First Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, 31000, People’s Republic of ChinaCorrespondence: Yibin Zhao, Email 510496772@qq.comAim: Increasing observational studies are revealing a positive correlation between body mass index (BMI) and the risk of Immune-mediated and Inflammatory Skin Diseases (IMID), however the causal relationship is not yet definite.Objective: The aim of the study was to conduct a two-sample Mendelian randomization (TSMR) to explore the potential causality between BMI, and IMID and biomarkers.Methods: The summary statistics for BMI (n = 322,154), at genome-wide significant level, were derived from the Genetic Investigation of Anthropometric Traits consortium (GIANT). The outcome data for IMID (Psoriasis, vitiligo, Atopic dermatitis (AD), acne, Bullous diseases, Dermatitis herpetiformis, Systemic lupus erythematosus (SLE), Alopecia Areata (AA), Hidradenitis suppurativa (HS) and Systemic sclerosis), and biomarkers were obtained from genome-wide association studies (GWAS). The TSMR analyses were performed in four methods, including inverse variance weighted (IVW) method, MR-Egger regression, the weighted median estimator (WME) and simple mode.Results: The IVW analysis showed that the per standard deviation (SD) increase in BMI increased a 57% risk of psoriasis. We also observed the suggestive evidence of a causal relationship between BMI and AD and HS. This analysis did not support causality of Vitiligo, Acne, Bullous pemphigoid, Dermatitis herpetiformis, SLE, AA and Systemic sclerosis. The higher risk of BMI may be explained by higher levels of Triglycerides, C-reactive protein (CRP), Interleukin 6, Erythrocyte sedimentation rate (ESR) and Neutrophil count. The high-density lipoprotein (HDL) has an inverse relationship with BMI. No influences were defined for Total cholesterol, low-density lipoprotein (LDL), Rheumatoid factor (RF), Basophil count and Eosinophil count.Conclusion: Our two-sample MR analysis proved the causal evidence for the associations between BMI and IMID, including psoriasis, AD and HS, which might be related to the elevated expression of biomarkers, including Triglycerides, CRP, Interleukin 6, ESR and neutrophil count.Keywords: Mendelian randomization, BMI, immune-mediated and inflammatory skin diseases, biomarkers, causal association